Examining The Relationship Between Profitability Indicators And Stock Market Valuation In Indonesian Banks - Mardia, Aina; Akbar, Taufiq; Abidin, Zaenal; Akbar, Muhammad (Westscience Press, 2025)
This study uses panel data regression with a sample size of 26 banks to investigate the impact that Return on Assets (ROA), Return on Equity (ROE), and Net Interest Margin (NIM) have on the stock prices of banking businesses that are listed on the Indonesia Stock Exchange throughout the period of 2019–2023. The results indicate that only ROE significantly influences stock prices, as it demonstrates the effectiveness of managing shareholders' equity in generating sustainable profits and acts as a crucial metric for investors evaluating a company's basic robustness and future potential. Conversely, ROA and NIM exhibited no substantial impact on stock prices, perhaps due to macroeconomic instability—exemplified by the COVID-19 pandemic—which prompted investors to prioritize external factors in their risk and return assessments. The results indicate that in times of systemic uncertainty, internal financial indicators had limited predictive capability for stock valuation, with investment decisions increasingly influenced by overarching market dynamics and external economic considerations.